2018
DOI: 10.1371/journal.pone.0191422
|View full text |Cite
|
Sign up to set email alerts
|

Individual differences in first- and second-order temporal judgment

Abstract: The ability of subjects to identify and reproduce brief temporal intervals is influenced by many factors whether they be stimulus-based, task-based or subject-based. The current study examines the role individual differences play in subsecond and suprasecond timing judgments, using the schizoptypy personality scale as a test-case approach for quantifying a broad range of individual differences. In two experiments, 129 (Experiment 1) and 141 (Experiment 2) subjects completed the O-LIFE personality questionnaire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 82 publications
1
9
1
1
Order By: Relevance
“…This result suggests that individual differences in sensitivity to timing relationships may be in part predicted by variance in personality features. This is inconsistent with work published since this project was completed (Corcoran et al, 2018), where no compelling relationship was found between measures of schizotypy and sensitivity to timing relationships. However, Corcoran et al used a different schizotypy measure, and different timing task (temporal bisection task in the supra-second scale).…”
Section: Schizotypal Personality Questionnairecontrasting
confidence: 99%
See 2 more Smart Citations
“…This result suggests that individual differences in sensitivity to timing relationships may be in part predicted by variance in personality features. This is inconsistent with work published since this project was completed (Corcoran et al, 2018), where no compelling relationship was found between measures of schizotypy and sensitivity to timing relationships. However, Corcoran et al used a different schizotypy measure, and different timing task (temporal bisection task in the supra-second scale).…”
Section: Schizotypal Personality Questionnairecontrasting
confidence: 99%
“…Schizotypy is a personality feature encompassing magical beliefs, odd perceptual experiences, paranoia, and more. While historically linked to schizophrenia, schizotypy is a continuous personality feature quantifiable even in healthy neuro-typical participants (Corcoran et al, 2018).…”
Section: Schizotypal Personality Questionnairementioning
confidence: 99%
See 1 more Smart Citation
“…The ability of subjects to identify and (re)produce brief temporal intervals is influenced by many factors whether stimulus, subject or task-based (Bruno et al, 2012;Corcoran et al, 2018;Jazayeri & Shadlen, 2010;Piras & Coull, 2011). Several reviews have comprehensively outlined the current state of empirical and theoretical development in time perception (Block & Grondin, 2014;Bruno & Cicchini, 2016;Grondin, 2008Grondin, , 2010Matthews, 2015;Matthews & Meck, 2014;Matthews & Meck, 2016;Meck & Ivry, 2016;Tsao et al, 2022); the aim here is not to repeat this information but to introduce and motivate what we believe is a novel and useful method to approach the study of brief to moderate temporal intervals and the metacognition of that perceptual experience.…”
Section: Introductionmentioning
confidence: 99%
“…1) La esquizotipia es considerada como un rasgo de personalidad que se distribuye de forma continua en la población general, sin ser necesariamente un indicio de psicopatología latente (Claridge y Beech, 1995). La esquizotipia ha despertado interés como un candidato potencial para predecir las diferencias individuales en la cognición temporal (Corcoran et al, 2018), debido a que involucra una variedad de características similares a las presentadas por pacientes psicóticos (Kwapil y Barrantes-Vidal, 2014).…”
Section: Discusión Del Diseño Y Aplicación De La Pruebaunclassified